2005
DOI: 10.1189/jlb.1204746
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for Notch ligand Delta-1 as a regulator of human Langerhans cell development from blood monocytes

Abstract: Human Langerhans cells (LCs) are of hematopoietic origin, but cytokine regulation of their development is not fully understood. Notch ligand Delta-1 is expressed in a proportion of the skin. Granulocyte-macrophage colony-stimulating factor (GM-CSF) and transforming growth factor-beta1 (TGF-beta1) are also secreted in the skin. We report here that Delta-1, in concert with GM-CSF and TGF-beta1, induces the differentiation of human CD14(+) blood monocytes into cells that express LC markers: CD1a, Langerin, cutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 52 publications
(58 reference statements)
6
62
1
Order By: Relevance
“…First, both cell types increased their pool of polymerized actin upon fMLF stimulation, suggesting that they were both responsive to chemokine stimulation. We then demonstrated that immature MDLCs and MDDCs responded to MIP-3b/CCL20 and not to MIP-3a/CCL19, in line with other studies (28). Both cell types also responded to MCP-1/CCL2 in accordance with their respective CCR2 expression levels.…”
Section: Mdlcs Respond To Tissue-and Lymphoid Organ-derived Chemokinessupporting
confidence: 75%
See 4 more Smart Citations
“…First, both cell types increased their pool of polymerized actin upon fMLF stimulation, suggesting that they were both responsive to chemokine stimulation. We then demonstrated that immature MDLCs and MDDCs responded to MIP-3b/CCL20 and not to MIP-3a/CCL19, in line with other studies (28). Both cell types also responded to MCP-1/CCL2 in accordance with their respective CCR2 expression levels.…”
Section: Mdlcs Respond To Tissue-and Lymphoid Organ-derived Chemokinessupporting
confidence: 75%
“…We assumed that other serum lipids such as high-density lipoproteins might be able to act similarly. Thus, serum lipids appeared to be responsible for a marked alteration of LC differentiation of monocytes in previous studies (28,31,32).…”
Section: Serum Lipids Impair Lc Differentiation Of Monocytes With Tgfmentioning
confidence: 99%
See 3 more Smart Citations